Peningkatan Produktivitas Ikan Lele dengan Teknik Bioflok pada Pokdatan Tikalak Wangi Pasia Laweh Kec. Palupuh Kab. Agam - Ifmalinda Ifmalinda; Silvia Rosa; Ashadi Hasan; Erigas Ekaputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
A community of Tikalak Wangi is a form of farmer group business carried out by the Nagari Pasia Laweh in order to increase productivity in the fisheries sector. Fish farming is part of any sector that has the potential to support the needs of the local community. The main problems currently exist for partners are a lack of facilities for cultivation, such as the use of bamboo as support for tarpaulin ponds, low quality of tarpaulin types, unstructured pond water circulation, and water pumps that are not optimal in regulating water. Furthermore, the quality of fish feed alternatives is still not maximized, and the business profits are not optimal due to no post-harvest processing. It was not easy to get a return on investment. Therefore, there needs to be a transfer of technology using the biofloc system to catfish farmers. This activity aimed to develop an alternative fish farming technology and apply fisheries skills for the community. This program resulted in the socialization and construction of catfish ponds with biofloc technology at the Tikalak Wangi Nagari Pasia Laweh Community Center, Palupuh District, Agam Regency.